OPTIMIZACIÓN DE LA CADENA DE DISTRIBUCIÓN DEL CONGLOMERADO PYMES DEL SECTOR CÁRNICO DE BOGOTÁ, D.C - GESTIÓN DE ALMACENES - ANGIE KATHERINE CRUZ FONTECHA; EDDIES ALEJANDRO ULLOA USME (Revista Ingeniería, Matemáticas y Ciencias de la Información, 2016)
This article refers to the project «Optimization of the supply chain cluster SMEs in the meat sector in Bogotá» focused on Chapter warehouse management, with emphasis on the optimization of the distribution chain, by combining optimization techniques and best business practices that incur the lowest total cost and provide the level of service planned. Below is a conceptual review where different types of storage are identified is presented, specific definitions such as warehouse, distribution center, among others, that in order to have a clear idea of the differences are discussed between each of these.